2009
DOI: 10.1111/j.1755-3768.2009.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of canalicular laceration repair using monocanalicular intubation with Monoka tubes

Abstract: ABSTRACT.Purpose: This study aimed to evaluate the clinical efficacy of canalicular laceration repair using monocanalicular intubation with Monoka tubes. Methods: A total of 36 single lacerated canaliculi were repaired using monocanalicular intubation with Monoka tubes, without mucosal anastomosis of the canaliculi, and were retrospectively reviewed. Demographic information, injury locations, associated ocular injuries, complications and outcomes were analysed. Results: Mean patient age was 34 years (range 1-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 13 publications
5
38
1
5
Order By: Relevance
“…[15] Success rate of monocanalicular intubation method has been reported in the range of 60% to 100%. [21][22][23]30,32,33] High rate of success has also been described in some studies conducted in our country. Argın et al, [12] Yaman et al, [29] and Oltulu et al reported success rate of 100%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[15] Success rate of monocanalicular intubation method has been reported in the range of 60% to 100%. [21][22][23]30,32,33] High rate of success has also been described in some studies conducted in our country. Argın et al, [12] Yaman et al, [29] and Oltulu et al reported success rate of 100%.…”
Section: Discussionmentioning
confidence: 95%
“…[5,12,13,16,[23][24][25][26][27][28][29][30][31][32][33] Bicanalicular intubation has rate ranging from 30% to 100%. [5,13,15,26,31] Jordan et al [5] reported success rate of 94% in large series, which included 222 bicanalicular intubations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the traditional bicanalicular stent has some disadvantages, including the potential for damage to the normal nasolacrimal duct and the Hasner valve. To avoid the drawbacks mentioned above, a number of therapeutic developments have been reported recently, such as the use of a pigtail probe in this setting, 8,9,12 but this technique is so difficult that its use has been discouraged because of possible damage to the common or uninjured canaliculus, leading to bypass formation, especially to the bicanalicular lacerations. To overcome the disadvantages of conventional BCI, improvements based on the use of silicone tubes have become increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Monocanalicular intubation with Monoka tubes offers an alternative method for the treatment of monocanalicular lacerations. 8 Recently, it has been reported that Mini-Monoka stent extrusions occur within 1 month and with an 11.1% extrusion rate, especially in upper canalicular lacerations, resulting in damage to the ocular surface. Therefore, this technique is not suitable for use in patients with combined upper and lower canalicular lacerations.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak günümüzde geçerli olan görüş kanalikülün obstrüksiyonunu önlemek için entübasyonun gerekli olduğu yönündedir. 6,[13][14][15] Silikon tüpler rahat yerleştirilmeleri ve çevreleyen dokularda reaksiyona yol açmamaları nedeniyle bu amaçla en yaygın kullanılan malzemelerdir. 14 …”
Section: Gereç Ve Yöntemunclassified